Vibronically coupled states: computational considerations and characterisation of vibronic and rovibronic spectroscopic parameters. Issue 2 (3rd April 2021) - Sharma, Ketan; Miller, Terry A.; Stanton, John F.
Abstract : The interaction of electronic and nuclear motion – broadly categorised as 'vibronic coupling' – plays a number of roles in areas that range from molecular dynamics to electronic spectroscopy. Additionally, these phenomena pose significant challenges to both computational electronic spectroscopy and quantum chemistry, as the usual approximations (Franck–Condon and Born–Oppenheimer) are often rendered unsatisfactory. After beginning with a broad overview of vibronic coupling effects and some computational strategies for characterising them, the review discusses how these effects are manifested in various types of spectra. Particular emphasis is given to fine-structure effects in Jahn–Teller systems that arise from couplings involving rotational, orbital and spin angular momenta. Unlike overall vibronic level structure, which has been quite well studied both theoretically and experimentally, these more subtle effects are seen only at high (rotationally-resolved) resolution, and are less well understood. The review gives a detailed description of the quantum-mechanical origin of these splittings and provides some computational strategies for predicting them. A broad overview is given of families of Jahn–Teller active molecules that have been investigated experimentally and theoretically. Detailed discussion is given for two JT-active radicals where theory and experiment are compared at both low and high resolution: cyclopentadienyl (C 5 H 5 ) and methoxy (CH 3 O).